Indian Intersectional Ecofeminism and Sustainability: A Study on Mayilamma: The Life of a Tribal Eco-Warrior and Jharkhandâ€™s Save the Forest Movement - Justin, Jyothi; Menon, Nirmala (Journal of Ecohumanism, 2022)
Ecofeminism in India, if approached and analysed non-intersectionally, will negate the struggles of the indigenous ecofeminists and their encounters. Therefore, it is important to look deeply into the indigenous ecofeminist initiatives in the country, especially by the Dalit and the Adivasi women. The paper attempts to engage with intersectional ecofeminism in India by focusing on the textual and the pragmatic aspects of the movement through specific case studies. â€œMayilamma: The Life of a Tribal Eco-Warriorâ€ and â€œSave the Forest the Movementâ€ in Jharkhand are closely read and analysed to understand the similarities and differences in the relationship between tribal women and their environment. This paper therefore tries to see the impact of ecofeminist activities of Adivasi or tribal women on battling environmental crisis and the reception of the same in policy making for sustainable development. The main aim of the paper is to understand the effect of intersectional ecofeminism in India on sustainable development. The paper also acknowledges the criticisms against intersectional ecofeminism and highlights the presence of alternate movements. This analysis further leads to the proposal of intersectional ecofeminism as a suitable model for sustainability in future.